Special considerations for orthodontic treatment in patients with root resorption - Haru S. Anggani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2010)
Background: Orthodontic treatment needs good consideration especially when there are unfavorable conditions for orthodontic treatment, such as periodontal diseases or tooth with root resorption. Root resorption should not become worse due to orthodontic treatment., All risk factors should be eliminated before orthodontic treatment is started. Otherwise, the goal of orthodontic treatment could be difficult to achieve because of poor dental and or oral health. Purpose: The purpose of this study was to learn more about mechanical factors that could worsen the root resorption that has already been there or even provoke root resorption to develop during orthodontic treatment. Reviews: Resorption of dental root surface is the condition in which cementum is depraved and the damage could also include dentin of dental root. It can occur either physiologically or pathologically due to some causes. The occurrence of the root resorption is suspected because of the biological factor, the tooth condition, the supportive tissue and the mechanical factors. Panoramic x-ray which routinely used to support diagnose in orthodontic cases, can detect root resorption in general, although sometimes periapical x-ray with parallel technique is needed to enhance the diagnosis. Before starting a treatment, the risk factors that suspected as the causes of root resorption should be eliminated, thus the mechanical treatment can be calculated. Conclusion: Orthodontic treatment in patient with root resorption should not escalate the root resorption which already occurs. The treatment should be done effectively by using optimal forces. Giving discontinued forces and avoiding intrusion and torque movements could reduce the risk factors of root resorption.Latar belakang: Keadaan gigi dan jaringan pendukung yang kurang menguntungkan bagi perawatan ortodontik hendaknya membutuhkan perhatian ekstra para klinisi. Kondisi tersebut misalnya adanya penyakit periodontal ataupun adanya gigi dengan resorpsi akar. Perawatan ortodontik yang dilakukan hendaknya tidak menambah parah resorpsi akar yang telah ada sebelumnya. Sebelum memulai perawatan, seluruh faktor yang diduga sebagai faktor resiko dihilangkan terlebih dahulu. Sebaliknya, tujuan perawatan ortodontik akan sulit dicapai akibat buruknya keadaan gigi dan jaringan pendukungnya. Tujuan: Mempelajari lebih jauh mengenai faktor mekanik yang dapat menyebabkan resorpsi akar atau bahkan memperparah terjadinya resorpsi akar yang telah ada akibat perawatan ortodontik. Tinjauan pustaka: Resorpsi permukaan akar gigi adalah kondisi rusaknya jaringan sementum akar gigi yang dapat berlanjut hingga ke jaringan dentin akar gigi. Resorpsi akar dapat terjadi secara fisiologis atau patologis. Terjadinya resorpsi akar ini diduga karena adanya faktor biologis, kondisi gigi dan jaringan pendukung serta adanya faktor mekanik. Foto ronsen panoramik yang rutin digunakan sebagai penunjang diagnosa pada perawatan ortodontik dapat mendeteksi secara umum adanya resorpsi akar, meskipun terkadang dibutuhkan foto ronsen periapikal teknik paralel untuk memperjelasnya. Sebelum memulai perawatan, faktor resiko yang diduga sebagai penyebab terjadinya resorpsi akar hendaknya dihilangkan lebih dahulu, baru kemudian mempertimbangkan biomekanika perawatan ortodontik. Kesimpulan: Perawatan ortodontik pada pasien dengan resorpsi akar hendaknya tidak memperparah resorpsi akar yang telah ada. Perawatan yang dilakukan haruslah seefektif dan seefisien mungkin dengan menggunakan gaya yang optimal. Selain itu pemberian gaya secara diskontinyu dan menghindaripemberian gaya intrust dan torquing dapat mengurangi terjadinya resorpsi akar gigi.